2019
DOI: 10.1186/s12889-019-7446-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-positive clients of female sex workers in Hunan Province, China: a mixed methods study assessing sexual relationships and risk behavior by type of partner

Abstract: Background In China, clients of female sex workers (CFSWs) have a low rate of condom use and a high prevalence of human immunodeficiency virus (HIV). However, little is known about the high-risk sexual behaviors of HIV-positive CFSWs. Methods In 2014, 327 CFSWs diagnosed with HIV for 6 months or longer completed a face-to-face questionnaire for a quantitative survey. In addition, 32 HIV-positive CFSWs were recruited to participate in in-depth interviews (18 participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Li et al, 2013; von Soest et al, 2020; L. Wang et al, 2020; Wu et al, 2019), we predicted that family support factors may affect the occurrence of high-risk sexual behavior of the sample through three intermediate paths: loneliness and life satisfaction, disposable economic conditions, and family responsibility and health belief (Figure 2).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Li et al, 2013; von Soest et al, 2020; L. Wang et al, 2020; Wu et al, 2019), we predicted that family support factors may affect the occurrence of high-risk sexual behavior of the sample through three intermediate paths: loneliness and life satisfaction, disposable economic conditions, and family responsibility and health belief (Figure 2).…”
Section: Discussionmentioning
confidence: 91%
“…Li et al, 2013;von Soest et al, 2020;L. Wang et al, 2020;Wu et al, 2019), we predicted that family support factors may affect the occurrence of high-risk sexual behavior of the sample through three intermediate paths: loneliness and life satisfaction, disposable economic conditions, and family responsibility and health belief (Figure 2). This study reported that unmarried, divorced/widowed without fixed sexual partners, and married but separated were the risk factors for the increase of commercial sex among rural elderly men.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There was likely some interweaving between these two populations. For example, some men might be engaged in both commercial and non-marital non-commercial heterosexual behaviors, which may transmit HIV from infected female sex workers (FSWs) to uninfected women in the general population, thereby spreading HIV from high-risk groups to the general population through heterosexual transmission ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…providing clean needles, methadone) to provide advice such as what gauge of needle to use depending on injection site, not to share water, and use a syringe only once. Drug use is associated with low likelihood of condom use and high likelihood of HIV infection among FSWs [ 83 ]. However, as this study has shown, most FSWs reported working when sober or with a maximum of two drinks, which suggests that the participants were engaging in less risky behavior than those in other studies.…”
Section: Discussionmentioning
confidence: 99%